Multicentre derivation and validation of a prognostic scoring system for mortality assessment in HIV‐infected patients with talaromycosis. Issue 2 (29th November 2020) - Qin, Yuanyuan; Zhou, Yihong; Lu, Yanqiu; Chen, Hui; Jiang, Zhongsheng; He, Kaiyin; Tian, Qun; Qin, Yingmei; Rao, Man; Harypursat, Vijay; Li, Huan; Chen, Yaokai
Abstract: Background: Although the widespread use of modern antiretroviral therapy (ART) has reduced the incidence of talaromycosis in people living with HIV, mortality remains as high as 20% in this population, even after appropriate antifungal treatment. Objectives: The objective of our study was to develop a risk assessment system for HIV‐infected patients with comorbid talaromycosis, in order to provide these patients with appropriate, effective and potentially life‐saving interventions at an early stage of their illness. Patients/Methods: This was a multicentre, retrospective cohort study conducted in China. We built a predictive model based on data from 11 hospitals, and a validated model using the data of 1 hospital located in an endemic area. Results: Forward stepwise multivariate statistical calculations indicated that age, aspartate aminotransferase/alanine transaminase ratio and albumin levels, and BUN levels were valid, independent predictors of the risk of death in HIV‐infected patients with talaromycosis. Our developed and validated risk scoring system is effective for the identification of HIV‐infected patients with talaromycosis at high risk of death at hospital admission ( p  < .001; AUC = 0.860). In our study, our risk prediction model provided functional and robust discrimination in the validation cohort ( p  < .001; AUC = 0.793). Conclusion: The prognostic scoring system for mortality assessment developed in the present study is an easy‐to‐use clinical tool designed to accurately assist clinicians in identifying high‐risk patients with talaromycosis.